Deteksi Molekuler Cucumber Mosaic Virus (Cmv) pada Tanaman Gamal (Gliricidia Sepium) Sebagai Barier pada Pertanaman Cabai - IDA BAGUS GDE PRANATAYANA; I GEDE RAI MAYA TEMAJA; KETUT YULIADHI; I DEWA NYOMAN NYANA; GEDE SUASTIKA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2014)
ABSTRACT Molecular Detection of Cucumber Mosaic Virus (CMV) In Gliricidia Plant (Gliricidia sepium) as Barrier at Chili pepper Crop The aims of the study are in order to symptoms characteristic identity the CMV infection on gliricidia plant and symptoms characteristic the CMV infection on chili pepper plant, and order to presence identity the CMV on gliricidia plant and presence the CMV on chili papper plant at Kerta village base on molecular analysis. The serology method was used to detect CMV virus is DAS-ELISA (Double Antibody Sandwich-Enzyme Link Immunosorbent Assay) and RT-PCR (Reverse Transcription-Polymerase Chain Reaction) was used for molecular analysis. The study include 1) the observation of mosaic in field, 2) preservation of plant samples (chili pepper and gliricidia) infected with mosaic virus, 3) serology test with DAS-ELISA, 4) molecular detection with RT-PCR. The research proved that symptoms characteristic the CMV infection on gliricidia plant identical with symptoms characteristic the CMV infection on chili pepper plant and presence the CMV on gliricidia plant identical with presence the CMV on chili pepper plant. symptoms of mosaic characteristic in gliricidia and chili pepper found on the field among others, mosaic (striped), contract and roll with variations of symptoms that light green mosaic with chlorotic and dark green mosaic symptoms in gliricidia and chili pepper plants. DAS-ELISA test results showed gamal and chili pepper samples infected positive of Cucumber Mosaic Virus (CMV). RT-PCR technique successfully amplify the target DNA fragment size of 657 bp. Based on these studies, the farmers need to be aware of the existence of the plant used as a plant barrier on chilli crop, because gliricidia potential as alternative hosts of CMV. Key word : Chili pepper, cucumber mosaic virus, gliricidia, molecular